Lamellarin 14, a derivative of marine alkaloids, inhibits the T790M/C797S mutant epidermal growth factor receptor. Issue 5 (24th March 2021) - Nishiya, Naoyuki; Oku, Yusuke; Ishikawa, Chie; Fukuda, Tsutomu; Dan, Shingo; Mashima, Tetsuo; Ushijima, Masaru; Furukawa, Yoko; Sasaki, Yuka; Otsu, Keishi; Sakyo, Tomoko; Abe, Masanori; et al.
Abstract: The emergence of acquired resistance is a major concern associated with molecularly targeted kinase inhibitors. The C797S mutation in the epidermal growth factor receptor (EGFR) confers resistance to osimertinib, a third‐generation EGFR‐tyrosine kinase inhibitor (EGFR‐TKI). We report that the derivatization of the marine alkaloid topoisomerase inhibitor lamellarin N provides a structurally new class of EGFR‐TKIs. One of these, lamellarin 14, is effective against the C797S mutant EGFR. Bioinformatic analyses revealed that the derivatization transformed the topoisomerase inhibitor‐like biological activity of lamellarin N into kinase inhibitor‐like activity. Ba/F3 and PC‐9 cells expressing the EGFR in‐frame deletion within exon 19 (del ex19)/T790M/C797S triple‐mutant were sensitive to lamellarin 14 in a dose range similar to the effective dose for cells expressing EGFR del ex19 or del ex19/T790M. Lamellarin 14 decreased the autophosphorylation of EGFR and the downstream signaling in the triple‐mutant EGFR PC‐9 cells. Furthermore, intraperitoneal administration of 10 mg/kg lamellarin 14 for 17 days suppressed tumor growth of the triple‐mutant EGFR PC‐9 cells in a mouse xenograft model using BALB/c nu/nu mice. Thus, lamellarin 14 serves as a novel structural backbone for an EGFR‐TKI that prevents the development of cross‐resistance against known drugs in this class. Abstract : The emergence of acquired resistance is a major concern associated with molecularly targeted kinase inhibitors. We report that the derivatization of the marine alkaloid topoisomerase inhibitor lamellarin N provides a structurally new class of epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs). One of these EGFR‐TKIs, lamellarin 14, is effective against the C797S mutant EGFR.